A taxonomy of impacts on clinical and translational research from community stakeholder engagement. (18th July 2019) - Stallings, Sarah C.; Boyer, Alaina P.; Joosten, Yvonne A.; Novak, Laurie L.; Richmond, Al; Vaughn, Yolanda C.; Wilkins, Consuelo H.
Abstract: Background: Community engagement is increasingly recognized as a valuable tool in clinical and translational research; however, the impact of engagement is not fully understood. No standard nomenclature yet exists to clearly define how research changes when community stakeholders are engaged across the research spectrum. This severely limits our ability to assess the value of community engagement in research. To address this gap, we developed a taxonomy for characterizing and classifying changes in research due to community engagement. Methods: Using an iterative process, we (a) identified areas of potential impact associated with community engagement from author experience, (b) categorized these in taxonomic bins based on research stages, (c) conducted semi‐structured interviews with researchers and community stakeholders, (d) validated the codebook in a sample dataset and (e) refined the taxonomy based on the validation. Community stakeholders were involved in every step of the process including as members of the primary study team. Results: The final taxonomy catalogues changes into eleven domains corresponding to research phases. Each domain includes 2‐4 dimensions depicting concepts within the domain's scope and, within each dimension, 2‐10 elements labelling activities through which community engagement could change research. Conclusions: Community engagement has great potential to enhance clinical and translational research. This taxonomy provides a common vocabulary and framework for understanding the impact of community engagement and suggests metrics for assessing the value of community engagement in research.